Teori Pemikiran Ekonomi Klasik "Invisible Hand" dan Relevansinya pada APBN di Indonesia (JEB17 : Jurnal Ekonomi dan Bisnis, 2024)
Adam Smith was a classical economist who was born in the middle of 18th century. The market mechanism regulates all of economic activities, such as production, distribution, and consumption. In the market mechanism, there is a “tug of war” in the process of economic activity thereby market will reach its equilibrium independently. The process, according to Smith, is controlled by an “invisible hand” that regulates market equilibrium. However, achieving a market balance by the “invisible hand” is a thing that very hard to proven. Market failure will occurred if the market is always left independently. Market failure can be marked by the appearance of imperfect competition market and externality. From here, it can be concluded that the role of The Government is considered very crucial to preserve the continuity of economic activity and to prevent market failure. In this case, APBN or State Budget is one of Indonesian Government’s efforts regulate economic activity. Thus, economic equilibrium can be gained and social welfare can be reached.